Global Islam: A Sociological Study of Muslim, Integration, and the Challenges of Multiculturalism in the 21st Century - Zaman, Hasanuz (Journal of Psychosociological Research in Family and Culture, 2025)
In the 21st century, globalization, migration, and multiculturalism have shaped the experiences of Muslim minorities in Western societies. This study explores the sociological aspects of Muslim integration, focusing on the challenges and opportunities faced by Muslim communities in multicultural settings. Using qualitative research methods, data were collected through in-depth interviews, focus group discussions (FGDs), case studies, and key-informant interviews (KII) with 15 Muslim immigrants from the United States, the United Kingdom, Switzerland, and Scotland. The findings reveal key barriers to integration, including employment discrimination, restrictions on religious clothing, difficulties in securing housing, limited access to halal food, and workplace discrimination. Furthermore, Islamophobia and negative media portrayals exacerbate societal tensions, leading to identity crises among young Muslims. Despite these challenges, Muslim communities employ various coping mechanisms, such as interfaith dialogues, advocacy initiatives, and community-driven support systems.